2017
DOI: 10.1016/j.juro.2017.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Stent Culture in Patients with Indwelling Ureteral Stents Prior to Ureteroscopy

Abstract: Only half of the patients with ureteral stents prior to ureteroscopy, and positive stent and urine cultures had similar pathogens in both cultures. Female gender and positive stent culture were associated with a higher risk of post-ureteroscopy sepsis in this population. Stent culture may direct the proper antibiotic treatment in patients with sepsis after ureteroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
4
16
1
Order By: Relevance
“…Usually, globulin plays an important role in immunity and inflammation. In the early phase of infection, the immunoglobulin level elevated rapidly (Nevo et al, 2017), which may account for the results in our study. A low AGR may indicate a susceptible state to infection.…”
Section: Discussionsupporting
confidence: 75%
“…Usually, globulin plays an important role in immunity and inflammation. In the early phase of infection, the immunoglobulin level elevated rapidly (Nevo et al, 2017), which may account for the results in our study. A low AGR may indicate a susceptible state to infection.…”
Section: Discussionsupporting
confidence: 75%
“…Usually, globulin plays an important role in immunity and inflammation. In the early phase of infection, the immunoglobulin level elevated rapidly 19 , which may account for the results in our study. A low AGR may indicate a susceptible state to infection.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, endoscopic procedures after stent removal increase the risk of infectious complications, even if preoperative UC is negative. Nevo et al (22) found SC positivity in 20.4% of their pre-stented patients prior to ureteroscopic surgery and concluded that positive SC was associated with a higher risk of post-URS sepsis in females and patient with comorbidity. They reported that positive SC was an independent predictor of post-URS sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Kehinde et al (12) showed that these comorbities were associated with significantly higher rates of bacteriuria and stent colonization. In several studies, sex and age were reported to be significant predisposing factors for stent colonization (12,22). On the contrary, Lifshitz et al (8) stated that age and sex had no influence on the incidence of bacteriuria and stent colonization.…”
Section: Discussionmentioning
confidence: 99%